TINJAUAN PELAKSANAAN RETENSI REKAM MEDIS DI RSUD DR. H. MOCH. ANSARI SALEH BANJARMASIN - Eka Rahma Ningsih; Husin Husin; Hijeratun Nisa (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Retention of medical records is carried out because medical records will continue to grow until the storage rack is full and there is no longer enough so that medical records will not be stored forever in the storage room. The results of observations in the preliminary study at RSUD Dr. H. Moch. Ansari Saleh, inactive medical records are still not stored in the inactive storage room as they should be. This study aims to review the retention of medical records in RSUD Dr. H. Moch. Ansari Saleh Banjarmasin from preparation, implementation to evaluation. This research method uses qualitative research with a case study design. The subjects of this study were taken using a purposive sampling technique with the subject of 1 Head of Medical Record and 3 Medical Record Officers at Dr. Hospital. H. Moch. Ansari Saleh Banjarmasin. The results of the study found that the preparation of medical record retention in RSUD Dr. H. Moch. Ansari Saleh Banjarmasin already has a policy, for the schedule there are still SOPs for retention, special human resources to carry out retention already exist, while the retention implementation facilities are still not sufficient to store inactive medical records. no treatment for 3 years and after being assessed for use, it will be destroyed using an incinerator machine, there are still obstacles, namely the limited space for storing inactive medical records. The conclusion of this study, the implementation of retention that is not in accordance with the existing SPO, an assessment is taken of a form that has value for storage, the obstacles found are the inactive medical record storage room in the active storage room.